Reshaping induced orientation composite material as well as preparation method and application thereof

By introducing dynamic covalent bonds into the resin matrix of the composite material and activate active bond exchange reactions, combined with external forces or displacement constraints, the orientation arrangement of the filling materials inside the composite material is realized, solving the complexity and inability to change the orientation method in the prior art. The problem of curing molding material orientation has obtained an efficient and economical method of preparing composite materials.

CN119410008AActive Publication Date: 2025-02-11XI AN JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411566979.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-11
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The existing composite material orientation methods are complex in operation, high equipment requirements, and cannot change the orientation of the filler material in the cured molded composite material.

Method used

By introducing dynamic covalent bonds into the resin matrix, the active bond exchange reaction is activated, and external force or displacement constraints are applied at a certain temperature, resulting in the reshaping of the material and inducing the directional arrangement of the filler material.

Benefits of technology

The filling materials in the molded composite material are redirected with ease of operation and inexpensive cost, and good mechanical properties and anisotropic properties are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410008A_ABST
    Figure CN119410008A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of composite materials, and particularly relates to a remolding induced orientation composite material as well as a preparation method and application thereof. The composite material is prepared according to the following steps: synthesizing a thermosetting resin-based composite material in which filler is uniformly distributed, wherein a resin matrix in the thermosetting resin-based composite material contains dynamic covalent bonds; the method comprises the following steps: adding a dynamic cross-linked network into a composite material, keeping for 5-200 minutes at 100-250 DEG C to activate the dynamic covalent bond exchange reaction in the composite material, and applying external force or displacement constraint at the temperature to induce the dynamic cross-linked network in the composite material to recombine and generate permanent deformation, thereby realizing the directional arrangement of the filling material in the composite material by the remodeling method. And the reshaped induced orientation composite material is obtained. The method realizes low-cost and convenient-to-operate directional arrangement of the filling materials in the composite material, and is expected to be further applied to preparation of various anisotropic composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite materials, and in particular relates to a composite material with reshaping-induced orientation and a preparation method thereof. The composite material is used for preparing anisotropic composite materials. Background Art

[0002] Thermosetting resin-based composite materials are mainly composed of thermosetting resins with covalent cross-linked networks as the matrix, and nanomaterials, short fibers, fiber cloth, etc. as fillers. They have excellent specific strength, specific stiffness, fatigue resistance, corrosion resistance and other properties, and are widely used in many fields such as machinery manufacturing, transportation, aerospace, national defense and military industry. For example, nanocomposites with montmorillonite added not only have excellent mechanical properties, but also have good heat resistance and gas barrier capabilities, and are widely used in today's automobile engine hood linings, fuel pipes, air intakes and other parts.

[0003] Filling materials such as nanomaterials, chopped fibers, and fiber cloth have excellent mechanical, thermal, and electrical properties along a specific orientation. Compared with traditional composite materials prepared by direct dispersion of fillers, the fillers inside the composite materials will produce anisotropy and obtain better mechanical, thermal, and electrical properties after oriented arrangement. Composite materials with anisotropy are used in many fields such as photovoltaics, sensing, energy transmission, and energy storage. For example, electrospun polymer fibers containing oriented nanorods are used for flexible independent surface enhanced Raman scattering.

[0004] At present, the following traditional directional arrangement methods can directional arrange the fillers inside the composite material according to the actual engineering application requirements: For fiber materials such as cellulose, uniaxial stretching can be used to induce fiber alignment, and external force can be applied along the direction in which the fibers inside the polymer need to be oriented. The stretching orientation method is simple to operate, but it is difficult to determine the stretching parameters and ensure the fiber orientation effect; an electric field is applied to a polymer solution containing conductive fillers such as metal fillers and carbon nanotubes, and the filling materials in the solution will be aligned between the electrodes at both ends. This method mainly utilizes the conductive properties of the filler itself. The charged material will move and directional according to the direction of the electric field; a suspension containing magnetic fillers such as metal oxide sheets is poured onto a substrate near a magnet or a magnetic field. At this time, the magnetic material is aligned along the direction of the magnetic field, and its magnetism is used to align under the action of a strong magnetic field. The material in the polymer solution can be oriented relatively quickly by using an electric field or a magnetic field, but this type of method has high equipment requirements and is only suitable for conductive or magnetic filling materials; electrospinning technology can also be used. The polymer solution is jet-spun under the action of an electric field, and the material in the solution will be arranged in an orderly manner along the direction of fiber generation. The electric field is mainly used to guide the polymer micro-jet, and the material in the jet is then oriented. The electrospinning method can make the filler be arranged along the direction of fiber generation, but it is difficult to obtain fiber filaments or short fibers separated from each other. The organic solvents of some electrospinning systems are expensive and difficult to recycle, which can easily cause environmental pollution. Therefore, some directional methods have high requirements for instruments and equipment, and other methods such as electric field induction are only suitable for conductive materials and are difficult to use for other types of filling materials. At present, the method of directional arrangement of filling materials is still under research at home and abroad, and this is still a difficult problem that needs to be solved. In addition to the above-mentioned nanocomposites, the fiber orientation in chopped fiber reinforced composites is also very important for their mechanical properties. For example, chopped carbon fibers themselves have excellent mechanical strength and good thermal stability, but similar to one-dimensional nanomaterials, the thermal conductivity is best along the axial direction. The traditional application of electric fields to induce carbon fiber alignment requires not only a high electric field strength, but also relatively complex instruments and equipment. Therefore, the development of new methods to control the orientation of chopped fibers in the composite matrix is ​​a major challenge.

[0005] In summary, it is particularly important to make the filling material inside the composite material have an orientation that is beneficial to production and application. Summary of the invention

[0006] In view of the problem that the traditional orientation method of composite materials has a complicated operation process, high requirements for instruments and equipment, and cannot change the orientation of the filling material in the solidified composite material, the present invention provides a method for preparing a composite material with reshaping induction orientation. The advantages of this method are simple operation process, low cost, and the ability to redirect the filling material in the formed composite material. As long as there are dynamic bonds in the resin matrix of the composite material that can undergo dynamic bond exchange reactions, such as ester bonds, urea bonds, boron oxygen bonds, borate bonds, amide bonds, imine bonds, thioether bonds, disulfide bonds or thioester bonds, the filling material can be redirected. The principle is that the dynamic bond exchange reaction inside the resin matrix leads to the reorganization of the network topology, causing permanent deformation of the material, and the reshaping will induce the filling material to produce a directional arrangement.

[0007] The present invention is implemented by the following technical solutions:

[0008] The present invention provides a method for preparing a composite material with reshaping-induced orientation, comprising the following steps:

[0009] Synthesizing a thermosetting resin-based composite material with uniformly distributed internal fillers, wherein the thermosetting resin matrix of the composite material contains dynamic covalent bonds;

[0010] The temperature is maintained at 100°C to 250°C for 5min to 200min to activate the dynamic covalent bond exchange reaction in the composite material, and then external force or displacement constraint is applied at this temperature to obtain permanent deformation through the reorganization of the dynamic cross-linking network inside the composite material. This reshaping method is used to achieve directional arrangement of fillers inside the composite material to obtain a reshaping-induced oriented composite material.

[0011] As a preferred embodiment of the present invention, the dynamic covalent bond is a dynamic covalent bond system of an ester bond, a urea bond, a borane bond, a borate bond, an amide bond, an imine bond, a thioether bond, a disulfide bond or a thioester bond.

[0012] As a preferred embodiment of the present invention, the method of applying external force or displacement constraint to perform reshaping is stretching, creep, stress relaxation or compression reshaping.

[0013] More preferably, when the material is reshaped by stretching, the strain rate is set to 0.01% / min to 0.2% / min, and the stretching time is 40min to 200min;

[0014] When the creep method is used for reshaping, the creep load is 0.1MPa~3MPa, the creep time is set to 40min~200min, and the creep recovery time is set to 20min~60min;

[0015] When the stress relaxation method is used for reshaping, the strain is set to 0.5% to 2% and the temperature range is 100°C to 250°C;

[0016] When the compression method is used for reshaping, the compression load is set to 1MPa~10MPa, and the experimental temperature is 100℃~250℃.

[0017] The purpose of applying external force is to maintain a small stress level and induce directional rearrangement of the filling material inside the specimen without destroying the structure of the specimen.

[0018] As a preferred embodiment of the present invention, the filler is a nano-metal material, a nano-non-metal material, a natural fiber, an inorganic fiber or a synthetic fiber.

[0019] More preferably, the filler is selected from gold nanowires, silver nanowires, gold nanorods, ferroferric oxide nanorods, silicon dioxide nanowires, carbon nanotubes, silicon nanocones, carbon nanobelts, boron nitride, graphene, polyaniline rods, cellulose, lignin, chitin, silk fibers, chopped carbon fibers, chopped glass fibers, boron fibers, ceramic fibers, metal fibers, chopped aramid fibers or liquid crystal polymer fibers.

[0020] The present invention also provides a composite material prepared according to any one of the above methods.

[0021] As a preferred embodiment of the present invention, the thermosetting resin-based composite material containing a uniformly distributed internal filler containing dynamic covalent bonds is synthesized according to the following steps:

[0022] After the filler material is mixed and dispersed with the epoxy resin, a catalyst and a polyacid or anhydride curing agent such as phthalic anhydride, glutaric anhydride or maleic anhydride are added to carry out a dynamic bond exchange reaction to obtain a composite material with uniformly dispersed internal fillers.

[0023] More preferably, the molar ratio of the epoxy group in the epoxy resin, the acyl group in the curing agent and the catalyst is 1.0-1.5:0.5-1.0:0.05-0.20.

[0024] The present invention also provides the use of the composite material in manufacturing load-bearing components in the field of transportation or in the field of aerospace, wherein the load-bearing components have the performance of bearing loads in a specific direction and being heat-insulating and gas-proof.

[0025] In the field of aerospace, there are parts that require bearing capacity in a specific direction, such as axial direction. Orienting the composite parts along the axial direction can improve their mechanical properties and better support the structure. The composite material with directional arrangement of internal fillers prepared by the present invention has better mechanical properties and can be used to prepare automobile engine hood linings, air intake holes or aircraft wall panels, wing skins and other load-bearing parts in the fields of transportation and aerospace.

[0026] The present invention has the following beneficial technical effects:

[0027] The preparation method of the composite material with reshaping induction orientation provided by the present invention can be widely used for the orientation of filling materials inside composite materials. The method has a convenient operation process, requires a moderate temperature, can reorient the filling materials in the solidified composite material, has good reliability, and can induce the directional arrangement of the filling materials by applying a small external force or displacement constraint at a specific temperature, and obtain good material properties. It breaks through the limitations of the traditional orientation method, which has a complex operation process, high cost, and cannot change the orientation of the internal filling materials of the solidified composite material.

[0028] The preparation method provided by the present invention has a wide range of application objects, and its orientation mechanism is that the dynamic bond exchange reaction inside the composite resin matrix reorganizes the network topology structure, triggering permanent deformation of the material, and the reshaping will induce the filling material to produce directional arrangement. The orientation method can be applied to the directional arrangement of various nano materials or fiber materials. The nano materials can be selected from nano metal materials or nano non-metal materials. The fiber materials can be selected from natural fibers, inorganic fibers or synthetic fibers. Nano metal materials such as gold nano wires, silver nano wires, gold nano rods, ferroferric oxide nano rods; nano non-metal materials such as silicon dioxide nano wires, carbon nano tubes, silicon nano cones, carbon nano belts, boron nitride, graphene, polyaniline rods; natural fibers such as cellulose, lignin, chitin, silk fibers; inorganic fibers such as chopped carbon fibers, chopped glass fibers, boron fibers, ceramic fibers, metal fibers; synthetic fibers such as chopped aramid fibers or liquid crystal polymer fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a flow chart for preparing the composite material with reshaping induced orientation in the present invention.

[0030] Figure 2 It is a diagram showing the mechanism of orientation of the filling material in the present invention.

[0031] Figure 3 It is the stretching and reshaping that induces the filling material to oriented arrangement.

[0032] Figure 4 It is the compression reshaping that induces the filling material to align in a directional manner.

[0033] Figure 5 It is the compression reshaping that induces the filling material to be oriented along any direction of curvature.

[0034] Figure 6 It is a graph of the tensile test results of the composite material before and after the internal filling material is oriented.

[0035] Figure 7 This is a transmission electron micrograph of an unoriented carbon nanotube reinforced composite material.

[0036] Figure 8This is a transmission electron microscope image of an oriented carbon nanotube reinforced composite material. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0038] Compared with traditional uniformly dispersed and oriented composite materials, the fillers inside the composite materials will produce anisotropy and obtain better mechanical, thermal and electrical properties after oriented arrangement. Composite materials with anisotropy are used in many fields such as photovoltaics, sensing, energy transmission, energy storage, etc. However, traditional orientation methods have high requirements for instruments and equipment and high cost of use. Some methods, such as electric field induction, are only applicable to conductive fillers and are difficult to use for other types of filler materials. In addition to common nanofillers, the fiber orientation in chopped fiber reinforced composite materials is also very important for its mechanical properties. For example, chopped carbon fibers themselves have excellent mechanical strength and good thermal stability, but similar to one-dimensional nanomaterials, the thermal conductivity of chopped fibers can only be achieved when they are axially oriented. The traditional application of electric field to induce the alignment of chopped carbon fibers not only requires a high electric field strength, but also the instruments and equipment are relatively complex. Therefore, it is a major challenge to develop a new method for controlling the orientation of chopped fibers in the composite matrix. Therefore, it is very important to make the filling materials inside the composite material have a certain orientation. It is necessary to develop a new filling material orientation method that is simple, efficient and low-cost.

[0039] The present invention provides a method for preparing a composite material with reshaping-induced orientation, which can be widely used in the preparation of anisotropic composite materials. The method comprises the following steps:

[0040] Synthesize thermosetting resin-based composite materials with uniform internal fillers, where the resin matrix contains dynamic covalent bonds; maintain at 100°C to 250°C for 5 to 200 minutes to activate the dynamic covalent bond exchange reaction in the composite material, and then apply external force or displacement constraints at this temperature to reorganize the dynamic cross-linked network inside the composite material to produce permanent deformation. This reshaping method achieves directional arrangement of the filling material in the composite material, and obtains a composite material with reshaping induced orientation.

[0041] Figure 1 That is, it is a flow chart of the directional arrangement of filling materials in the reshaping-induced composite material provided by the present invention, synthesizing a composite material sample with randomly distributed internal filling materials, and inducing the filling materials to orientate by slow stretching, creep, stress relaxation or hot pressing reshaping at high temperature, and finally realizing the orderly directional arrangement of the fillers.

[0042] Figure 2This is a diagram of the mechanism of the orientation of the filling material in the present invention. In the temperature range of 100℃ to 250℃, the composite material gradually enters the viscous flow state. As the dynamic bond exchange reaction proceeds rapidly, the dynamic network topology is reorganized, causing the material to produce permanent deformation. Under the induction of external force or displacement, the filling material will be oriented along the direction of the reorganization movement of the dynamic network. When the temperature drops and the external force is removed, the composite material retains the permanent deformation produced. At this time, a new dynamic network structure is formed inside, and the filling material will maintain the state after oriented arrangement.

[0043] In addition, in the present invention, as long as there are dynamic covalent bonds in the resin matrix, a dynamic bond exchange reaction can occur, and the directional arrangement of the filling material can be achieved. The dynamic covalent bonds include ester bonds, urea bonds, boron oxygen bonds, borate ester bonds, amide bonds, imine bonds, thioether bonds, disulfide bonds or thioester bonds. Dynamic covalent bond system.

[0044] The filling material in the present invention can be a variety of nano materials or fiber materials, such as nano metal materials, nano non-metal materials, natural fibers, inorganic fibers or synthetic fibers.

[0045] Exemplarily, the filling material can be selected from nanometal materials such as gold nanowires, silver nanowires, gold nanorods, ferroferric oxide nanorods; nanononmetal materials such as silica nanowires, carbon nanotubes, silicon nanocones, carbon nanobelts, boron nitride, graphene, polyaniline rods; natural fibers such as cellulose, lignin, chitin, silk fibers; inorganic fibers such as chopped carbon fibers, chopped glass fibers, boron fibers, ceramic fibers, metal fibers; synthetic fibers such as chopped aramid fibers or liquid crystal polymer fibers.

[0046] The filling material orientation method provided by the present invention has a mechanism of activating the bond exchange reaction of the dynamic network in the resin matrix at a certain temperature, causing permanent deformation and remodeling, and the filling material is arranged in a directional manner along the direction of the dynamic network reorganization movement. Therefore, conditions such as temperature, load level, and loading time determine the final directional arrangement effect of the filling material. For example, at a lower temperature such as 100°C and a smaller load such as 0.1MPa, the dynamic bond exchange reaction rate inside the matrix is ​​slow, and a longer loading time is required to achieve a good orientation effect; similarly, when the temperature is higher such as 200°C and the load is larger than 0.5MPa, it only takes 40 minutes to achieve a significant orientation effect. The experimental conditions of this orientation method should be changed according to different material preparations and preparation ratios.

[0047] The filling material orientation method of the present invention can be widely used in the orientation of filling materials in composite materials and the preparation of anisotropic composite materials. It requires moderate temperature and simple processing flow, can redirect the filling materials in the solidified composite materials, and has good reliability.

[0048] The following describes the invention in conjunction with specific embodiments.

[0049] Example 1

[0050] A method for preparing a composite material with reshaping-induced orientation comprises the following steps:

[0051] (1) Preparation of composite materials with uniform dispersion of internal filling materials

[0052] In this embodiment, the filling material is firstly uniformly dispersed in the polymer solution. Commonly used dispersion methods include physical dispersion and chemical dispersion. Physical dispersion methods include grinding, ultrasound, mechanical stirring, etc., and chemical dispersion methods include strong acid and strong alkali washing, etc. Dispersants can also be added to assist the filling material to obtain uniform dispersion. The added filling material is carbon nanotubes, for example, the carbon nanotubes have a diameter of 10 to 30 nanometers, a length of 10 to 30 microns, and a content of 95wt%.

[0053] The main components of the resin matrix of the composite material are bisphenol A diglycidyl ether monomer, glutaric anhydride and catalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene;

[0054] Add carbon nanotubes to bisphenol A diglycidyl ether monomer, stir at 110°C for 30 minutes until uniform, and perform ultrasonic dispersion treatment for 40 minutes under ice bath conditions. The purpose of this step is to ensure that the carbon nanotubes are uniformly dispersed in the solution. After the ultrasonic treatment, the catalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene is added to the solution, and the mixed solution with 1,5,7-triazabicyclo[4.4.0]dec-5-ene is continued to be stirred at 110°C for 30 minutes until the catalyst is completely dissolved. Cool down to 70°C, add glutaric anhydride to the mixed solution and stir quickly. The bisphenol A diglycidyl ether monomer, glutaric anhydride and catalyst are added according to the molar ratio of epoxy functional group: acyl functional group: catalyst of 1:1:0.1. Finally, the bubbles in the mixed solution are removed in a vacuum drying oven, and the mixed solution is poured into a pre-treated mold and placed in an oven for curing. The curing conditions are to maintain it at 100°C for 4 hours, raise the temperature to 130°C and continue to maintain it for 4 hours to obtain a composite material with uniformly dispersed internal filling materials.

[0055] (2) Slow stretching induces directional arrangement of filling materials

[0056] The composite material obtained in (1) was stretched using a load large deformation stretching machine Zwick, and the strain rate of the stretching machine was set to 0.1% / min. After being kept at 180°C for 10 minutes, it was slowly stretched for 40 minutes at the same temperature, and kept for 30 minutes after unloading to obtain a composite material with reshaping induced orientation. The experimental principle is as follows Figure 3 shown.

[0057] Under the induction of high temperature and external force, the bond exchange reaction inside the composite resin matrix is ​​activated, the dynamic network topology is changed, and the permanent deformation of the material is achieved. This shaping method allows the filling material to be oriented along with the dynamic network reorganization movement.

[0058] Example 2

[0059] A method for preparing a composite material with reshaping-induced orientation comprises the following steps:

[0060] Slow stretching induces directional alignment of filling materials

[0061] The composite material obtained in Example 1 was stretched using a load large deformation stretching machine Zwick, the strain rate of the stretching machine was set to 0.01% / min, and after being kept at 100°C for 10 minutes, it was slowly stretched for 200 minutes at the same temperature, and kept warm for 30 minutes after unloading to obtain a composite material with reshaping induced orientation. The experimental principle is as follows: Figure 3 shown.

[0062] Example 3

[0063] A method for preparing a composite material with reshaping-induced orientation comprises the following steps:

[0064] Slow stretching induces directional alignment of filling materials

[0065] The composite material obtained in Example 1 was stretched using a load large deformation stretching machine Zwick, with the strain rate of the stretching machine set to 0.2% / min. After being kept at 250°C for 5 minutes, it was slowly stretched for 100 minutes at the same temperature, and kept for 30 minutes after unloading to obtain a composite material with reshaping induced orientation. The experimental principle is as follows: Figure 3 shown.

[0066] Example 4

[0067] A method for preparing a composite material with reshaping-induced orientation comprises the following steps:

[0068] Slow stretching induces directional alignment of filling materials

[0069] The composite material obtained in Example 1 was stretched using a load large deformation stretching machine Zwick, with the strain rate of the stretching machine set to 0.05% / min. After being kept at 180°C for 10 minutes, it was slowly stretched for 150 minutes at the same temperature, and kept for 30 minutes after unloading to obtain a composite material with reshaping induced orientation. The experimental principle is as follows: Figure 3 shown.

[0070] Example 5

[0071] A method for preparing a composite material with reshaping-induced orientation comprises the following steps:

[0072] Slow stretching induces directional alignment of filling materials

[0073] The composite material obtained in Example 1 was used, and a tensile load was applied to the composite material using a force loading mode. The force loading rate can vary in the range of 2N / min to 15N / min. The specific force loading rate selected in this embodiment is 3N / min. After being kept warm for 10 minutes at a temperature of 100°C, the composite material was slowly stretched for 100 minutes at the same temperature. After unloading, the composite material was kept warm for 30 minutes to obtain a reshaped induced orientation composite material. The experimental principle is as follows Figure 3 shown.

[0074] Example 6

[0075] A method for preparing a composite material with reshaping-induced orientation comprises the following steps:

[0076] Creep-induced orientation of filler materials

[0077] The composite material obtained in Example 1 was used, and a load large deformation tensile machine Zwick was used to apply force constraints at both ends of the experimental sample. After keeping the temperature at 180°C for 10 minutes, a load of 0.2 MPa was applied, the creep time was 40 minutes, and the creep recovery time was 30 minutes. The principle is as follows: Figure 3 shown.

[0078] Example 7

[0079] A method for preparing a composite material with reshaping-induced orientation, which is different from Example 6 only in that:

[0080] Creep-induced orientation of filler materials

[0081] The composite material obtained in Example 1 was used, and force constraints were applied to both ends of the experimental sample using a load large deformation tensile machine Zwick. After the temperature was 140°C and the temperature was kept for 10 minutes, a load of 0.3 MPa was applied, and creep was carried out for 200 minutes, with a creep recovery time of 60 minutes.

[0082] Example 8

[0083] A method for preparing a composite material with reshaping-induced orientation, which is different from Example 6 only in that:

[0084] Creep-induced orientation of filler materials

[0085] The composite material obtained in Example 1 was used, and force constraints were applied to both ends of the experimental sample using a load large deformation tensile machine Zwick. After the temperature was 250°C and the temperature was kept for 5 minutes, a load of 0.1 MPa was applied, the creep time was set to 80 minutes, and the creep recovery time was set to 20 minutes.

[0086] Examples 6 to 8 show that as the temperature rises, the dynamic network inside the composite material is gradually activated, and the faster the creep rate, the faster the orientation rate of the internal filling material; and the irreversible deformation of the composite material is also increasing. This reshaping method allows the directional arrangement of the filling material to be retained. And at a load level of 0.2MPa at 180°C, the carbon nanotubes inside the sample containing 2wt% carbon nanotubes can achieve a good directional arrangement effect within 40 minutes. It should be noted that the external force conditions set by creep should not be too large, otherwise the material will undergo irreversible large deformation or even fracture damage.

[0087] Example 9

[0088] A method for preparing a composite material with reshaping-induced orientation comprises the following steps:

[0089] Stress relaxation induces directional alignment of filler materials

[0090] The composite material obtained in Example 1 was kept at 200°C for 10 minutes, and then a large load strain tensile machine Zwick was used to apply displacement constraints on both ends of the experimental sample. The relaxation test temperature was set to 200°C, and the sample strain was set to 1%. The experimental principle is as follows: Figure 3 The specimen is reshaped by stress relaxation, thereby inducing the directional arrangement of the filling material.

[0091] Example 10

[0092] A method for preparing a composite material with reshaping-induced orientation, which is different from Example 9 only in that:

[0093] Stress relaxation induces directional alignment of filler materials

[0094] The composite material obtained in Example 1 was kept at 250°C for 5 minutes, and then a load large deformation tensile machine Zwick was used to apply displacement constraints on both ends of the experimental sample. The relaxation test temperature was set to 250°C, and the sample strain was set to 0.5%. The experimental principle is as follows: Figure 3 The specimen is reshaped by stress relaxation, thereby inducing the directional arrangement of the filling material.

[0095] Embodiment 11

[0096] A method for preparing a composite material with reshaping-induced orientation, which is different from Example 9 only in that:

[0097] Stress relaxation induces directional alignment of filler materials

[0098] The composite material obtained in Example 1 was kept at 180°C for 5 minutes, and then a large load strain tensile machine Zwick was used to apply displacement constraints on both ends of the experimental sample. The relaxation test temperature was set to 180°C, and the sample strain was set to 2%. The experimental principle is as follows: Figure 3 The specimen is reshaped by stress relaxation, thereby inducing the directional arrangement of the filling material.

[0099] The experimental results show that as the temperature increases, the relaxation time of the composite materials provided by Examples 9 to 11 becomes shorter and shorter, which indicates that the dynamic network inside the composite material is activated, the dynamic bond exchange reaction becomes faster, and the network structure is reorganized faster. This reshaping method allows the filling material to be arranged in a directional manner faster along the direction of the displacement constraint.

[0100] Example 12

[0101] A method for preparing a composite material with reshaping-induced orientation comprises the following steps:

[0102] Compression deformation induces directional alignment of filler materials

[0103] The composite material in Example 1 was maintained at 180°C for 10 min, and then a large strain tensile machine Zwick was used to compress the test sample at an experimental temperature of 180°C and an external load of 3 MPa. The experimental principle is as follows: Figure 4 The specimen is reshaped by compression, thereby inducing a directional arrangement of the filling material.

[0104] Embodiment 13

[0105] A method for preparing a composite material with reshaping-induced orientation comprises the following steps:

[0106] Compression deformation induces directional alignment of filler materials

[0107] The composite material in Example 1 was kept at 100°C for 5 minutes, and then a large strain tensile machine Zwick was used to compress the test sample at an experimental temperature of 100°C and an external load of 10 MPa. The experimental principle is as follows: Figure 4 The specimen is reshaped by compression, thereby inducing a directional arrangement of the filling material.

[0108] Embodiment 14

[0109] A method for preparing a composite material with reshaping-induced orientation comprises the following steps:

[0110] Compression deformation induces directional alignment of filler materials

[0111] The composite material in Example 1 was maintained at 250°C for 5 minutes, and then a large strain tensile machine Zwick was used to compress the test sample at an experimental temperature of 250°C and an external load of 1 MPa. The experimental principle is as follows: Figure 4 The specimen is reshaped by compression, thereby inducing a directional arrangement of the filling material.

[0112] It is known from the experimental results of Examples 12 to 14 that after compression, the filling materials inside the composite material are all oriented and arranged in a manner perpendicular to the axial compression direction.

[0113] Embodiment 15

[0114] A method for preparing a composite material with reshaping-induced orientation comprises the following steps:

[0115] Compression reshaping induces the filling material to align along any curvature direction

[0116] The composite material in Example 1 was maintained at 200°C for 5 minutes, and then the flat sample was hot-pressed for 2 hours using a hot pressing molding machine and a mold with a certain curvature under the conditions of a temperature of 200°C and a pressure of 3 MPa. The experimental process is as follows: Figure 5 As shown. After the composite material is stretched or compressed at high temperature, it will produce significant irreversible deformation. This permanent deformation can orient the filler material in the composite material and completely reshape the shape of the composite material, thereby producing anisotropic composite materials.

[0117] The experimental results show that composite materials can not only be reshaped into different shapes, such as reshaping a flat specimen into a curved specimen with a certain curvature, but also the filling material inside the composite material will be oriented along the curvature direction.

[0118] Example 16

[0119] A method for preparing a composite material with reshaping induced orientation, which is different from Example 1 only in that the filling material is silver nanowires when preparing the composite material with uniformly dispersed internal filling material, and bisphenol A diglycidyl ether monomer, glutaric anhydride and catalyst are added according to the molar ratio of epoxy functional group: acyl functional group: catalyst of 1.5:1:0.1.

[0120] Embodiment 17

[0121] A method for preparing a composite material with reshaping induced orientation, which is different from Example 1 only in that when preparing the composite material with uniformly dispersed internal filling material, the filling material is cellulose, and bisphenol A diglycidyl ether monomer, glutaric anhydride and catalyst are added according to the molar ratio of epoxy functional group: acyl functional group: catalyst of 1.5:0.5:0.1.

[0122] Embodiment 18

[0123] A method for preparing a composite material with reshaping induced orientation, which is different from Example 1 only in that when preparing the composite material with uniformly dispersed internal filling material, the filling material is chopped carbon fiber, and bisphenol A diglycidyl ether monomer, glutaric anhydride and catalyst are added according to the molar ratio of epoxy functional group: acyl functional group: catalyst of 1.0:0.5:0.2.

[0124] Embodiment 19

[0125] A method for preparing a composite material with reshaping induced orientation, which is different from Example 1 only in that when preparing the composite material with uniformly dispersed internal filling material, the filling material is graphene, and bisphenol A diglycidyl ether monomer, glutaric anhydride and catalyst are added according to the molar ratio of epoxy functional group: acyl functional group: catalyst of 1.0:0.5:0.2.

[0126] Since Examples 1 to 19 all obtained composite materials with directional arrangement of internal filling materials, the present invention only takes the composite material with directional arrangement of internal filling materials obtained in Example 1 as an example to illustrate the stretching-induced material anisotropy and the orientation of the internal filling material from both macroscopic and microscopic perspectives.

[0127] 1. Tensile test

[0128] The composite materials before and after the tensile-induced internal filling material orientation arrangement in Example 1 were subjected to tensile tests using a load large deformation tensile machine Zwick, with the tensile rate set to 3 mm / min. Figure 6 shown.

[0129] The results show that the tensile strength of the composite material with uniform internal filling material dispersion (unoriented) is 42.6±1.9MPa, and the Young's modulus is 1709.6±15.4MPa; the tensile strength of the composite material perpendicular to the induced direction (after orientation) is 46.7±0.2MPa, and the Young's modulus is 1866.2±16.8MPa; the tensile strength of the composite material along the induced direction (after orientation) is 51.1±0.8MPa, and the Young's modulus is 1872.5±21.8MPa. It shows that the strength of the composite material with directional arrangement of internal filling material provided by the present invention is significantly improved along the tensile direction, and the composite material has better mechanical properties.

[0130] 2. Transmission electron microscopy observation

[0131] Transmission electron microscopy observations were performed on the composite material with directional arrangement of internal filling materials induced by stretching in Example 1 and the composite material without stretching. Figures 7-8 As shown. Figure 7 It can be seen that at a scale of 200 nm, the filling materials inside the composite material are in a scattered state and have not yet been oriented. Figure 8 It can be seen that at a scale of 200 nm, it can be observed that the internal filling material exhibits obvious directional arrangement characteristics.

[0132] The above implementation cases are only preferred embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention has been disclosed as above with preferred embodiments, they are not intended to limit the present invention. Therefore, any simple modification, equivalent changes and modifications made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a composite material with reshaping-induced orientation, characterized in that: The steps include: Synthesizing a thermosetting resin-based composite material with uniformly distributed internal fillers, wherein the resin matrix in the thermosetting resin-based composite material contains dynamic covalent bonds; The temperature is maintained at 100°C to 250°C for 5min to 200min to activate the dynamic covalent bond exchange reaction in the composite material, and then external force or displacement constraint is applied at this temperature to induce the reorganization of the dynamic cross-linking network inside the composite material to obtain permanent deformation. This reshaping method is used to achieve the directional arrangement of the filler inside the composite material to obtain a reshaping-induced oriented composite material.

2. The method for preparing a composite material with reshaping-induced orientation according to claim 1, characterized in that: The dynamic covalent bond is a dynamic covalent bond system of an ester bond, a urea bond, a boron oxygen bond, a borate ester bond, an amide bond, an imine bond, a thioether bond, a disulfide bond or a thioester bond.

3. The method for preparing a composite material with reshaping-induced orientation according to claim 1, characterized in that: The methods of applying external forces or displacement constraints to reshape are stretching, creep, stress relaxation or compression reshaping.

4. The method for preparing a composite material with reshaping-induced orientation according to claim 3, characterized in that: When reshaping by stretching, the strain rate is set to 0.01% / min to 0.2% / min, and the stretching time is 40min to 200min; When the creep method is used for reshaping, the creep load is 0.1MPa~3MPa, the creep time is set to 40min~200min, and the creep recovery time is set to 20min~60min; When the stress relaxation method is used for reshaping, the strain is set to 0.5% to 2% and the experimental temperature is 100°C to 250°C; When the compression method is used for reshaping, the compression load is set to 1MPa~10MPa, and the experimental temperature is 100℃~250℃.

5. The method for preparing a composite material with reshaping-induced orientation according to claim 1, characterized in that: The filler is nano-metal material, nano-non-metal material, natural fiber, inorganic fiber or synthetic fiber.

6. The method for preparing a composite material with reshaping-induced orientation according to claim 5, characterized in that: The filler is selected from gold nanowires, silver nanowires, gold nanorods, ferroferric oxide nanorods, silicon dioxide nanowires, carbon nanotubes, silicon nanocones, carbon nanobelts, boron nitride, graphene, polyaniline rods, cellulose, lignin, chitin, silk fibers, chopped carbon fibers, chopped glass fibers, boron fibers, ceramic fibers, metal fibers, chopped aramid fibers or liquid crystal polymer fibers.

7. A composite material prepared according to the method described in any one of 1 to 6 above.

8. Use of the composite material according to claim 7 in manufacturing load-bearing components in the field of transportation or in the field of aerospace, characterized in that: The bearing component has the performance of bearing load in a specific direction and insulating and blocking heat and gas.

9. The use according to claim 8, characterized in that: The composite material is used to manufacture hood linings, air intakes, aircraft panels or wing skins of automobiles.

Citation Information

Patent Citations

  • High-strength self-repairing elastomer material and preparation method thereof

    CN115181347A

  • Welding method of epoxy resin and epoxy resin-based composite material

    CN118221992A

  • Recyclable, repairable and remodelable double-dynamic crosslinking epoxy resin composite material as well as preparation method and application thereof

    CN118496472A

  • Dynamic strain hardening in polymer nanocomposites

    US20130069271A1